1992
DOI: 10.3109/02652049209021248
|View full text |Cite
|
Sign up to set email alerts
|

In vivodistribution and antitumour activity of liposomal 3′,5′-O-dipalmitoyl-5-fluoro-2′-deoxyuridine

Abstract: 3',5'-O-dipalmitoyl-5-fluoro-2'-deoxyuridine (FUdR-dipalmitate), a lipophilic prodrug of 5-fluoro-2'-deoxyuridine (FUdR), was incorporated in different types of liposomes. The in vivo distribution and intrahepatic deacylation of liposomal FUdR-dipalmitate was found to be strongly dependent on liposome composition and on drug to lipid ratio. The use of fluid-type liposomes (egg PC/PS/CHOL) rendered FUdR-dipalmitate more susceptible to enzymatic breakdown than solid-type liposomes (DSPC/DPPG/CHOL). A decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The AUC is generally higher for liposomes prepared with high phase transition lipids such as DSPC (T m = 55.1 °C [74]). Floxuridine-dipalmitate loaded into liquid crystalline EPC liposomes was cleared faster than when incorporated into more rigid DSPC vesicles [75].…”
Section: Impact Of the Liposomal Carrier On L-ldc Pksmentioning
confidence: 89%
See 1 more Smart Citation
“…The AUC is generally higher for liposomes prepared with high phase transition lipids such as DSPC (T m = 55.1 °C [74]). Floxuridine-dipalmitate loaded into liquid crystalline EPC liposomes was cleared faster than when incorporated into more rigid DSPC vesicles [75].…”
Section: Impact Of the Liposomal Carrier On L-ldc Pksmentioning
confidence: 89%
“…For instance, the incorporation of a phospholipid-anchored LDC of 2'-C-cyano-2'-deoxy-1-β-D-arabino-pentofuranosylcytosine was reported to reduce the blood circulation time of liposomes compared to unloaded vesicles [33]. Similarly, conventional liposomes loaded with 10 mol% floxuridine-dipalmitate were cleared faster than those containing 2 mol% of the drug [75].…”
Section: Impact Of the Liposomal Carrier On L-ldc Pksmentioning
confidence: 99%
“…In a previous study high in vivo toxicity was observed for a similar prodrug, 3′,5′-dipalmitoyl-FUdR. 19,21 In our model and at the dosage used (100 µg), compound 6 showed evident signs of toxicity and no antitumor activity. In contrast, both the liposomes and the immunoliposomes bearing drug 6 eradicated the tumor nodules progressively in a time-dependent manner, reaching maximum effect on day 27 postgraft.…”
Section: Discussionmentioning
confidence: 73%
“…For this reason, FUdR has usually been incorporated into the lipid vesicle as lipophilic prodrug. [19][20][21][22] To increase delivery efficiency, liposomes have been conjugated with monoclonal antibodies; the resulting immunoliposomes have been studied to establish their potential as a tool to achieve more site-specific drug delivery. 23 We are particularly interested in using a model of intraabdominal-disseminated human colorectal cancer, intraperitoneally grafted in athymic mice, as a means to prove the efficacy of new drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…For non-targeted, non-long-circulating (conventional) liposomes containing FUdR-dP, increased toxicity compared to free FUdR has been described (Supersaxo et al, 1988;Van Borssum Waalkes et al, 1992). This was attributed to the sustained release of FUdR from Kupffer cells after uptake of the FUdR-dP-liposomes .…”
Section: Discussionmentioning
confidence: 98%